PENGARUH PERIODE IMBIBISI TERHADAP INDUKSI EMBRIO SOMATIK DUA VARIETAS KACANG TANAH (ARACHIS HYPOGEA L.) SECARA IN VITRO - Edy, Akari; Hendrady, Resmia Fajarwati; Utomo, Setyo Dwi (JURNAL AGROTROPIKA, 2013)
The objectives of the experiment were to (1) investigate the effect of seed imbibitions period on inducing somatic embryo of peanut varieties, (2) determine the best imbibitions period. The experiment was arranged in a completely randomized design with eight replicates. Each experimental unit consisted of culture bottles each of which contained five leaflet explants. Two varieties of peanut of var. Kancil and var. Singa were imbibed in water for 0, 20, 40, and 60 hours before sown aseptically on MS medium. Data were subjected to analysis of variance and if there was any significant F result (s), the means were separated using least significant difference at P? 0.05. Results of the experiment showed that: (1) Imbibitions period had significant effect on inducing somatic embryo of peanut varieties, (2) For var. Kancil, the best embryo somatic numbers and embryonic callus percentage were produced by 40 hours of imbibitions, while for var. Singa were produced by 20 hours imbibitions.  Key words: peanut, imbibitions period, MS medium, somatic embryo.